Cycloastragenol Attenuates Osteoclastogenesis and Bone Loss by Targeting RANKL-Induced Nrf2/Keap1/ARE, NF-κB, Calcium, and NFATc1 Pathways - Wang, Gang; Ma, Chao; Chen, Kai; Wang, Ziyi; Qiu, Heng; Chen, Delong; He, Jianbo; Zhang, Cheng; Guo, Ding; Lai, Boyong; Zhang, Shuangxiao; Huang, Linfeng; et al. (Frontiers in Pharmacology, 2022)
Osteoporosis, which typically affects postmenopausal women, is an osteolytic disease due to over activation of osteoclast. However, current drugs targeting osteoclast inhibition face various side effects, making natural compounds with great interest as alternative treatment options. Cycloastragenol (CAG) is a triterpenoid with multiple biological activities. Currently, CAG’s activity against aging-related osteoporosis was reported, but the mechanisms of actions for the activities were not understood. This study demonstrated that CAG dose-dependently inhibited osteoclast formation in receptor activator of nuclear factor-κB ligand (RANKL)-stimulated bone marrow macrophage (BMMs). Mechanism studies showed that CAG inhibited NF‐κB, calcium, and nuclear factor of activated T cells 1 (NFATc1) pathways. Additionally, CAG also promoted the nuclear factor-erythroid 2-related factor 2 (Nrf2)/Kelch-like ECH-associated protein 1 (Keap1)/anti-oxidative response element (ARE) pathway that scavenges reactive oxygen species (ROS). Furthermore, CAG was also found to prevent bone loss of postmenopausal osteoporosis (PMO) in a preclinical model of ovariectomized (OVX) mice. Collectively, our research confirms that CAG inhibits the formation and function of osteoclasts by regulating RANKL-induced intracellular signaling pathways, which may represent a promising alternative for the therapy of osteoclast-related disease.